Nonnegative solutions for a system of impulsive BVPs with nonlinear nonlocal BCs - Infante, Gennaro; Pietramala, Paolamaria (Nonlinear Analysis: Modelling and Control, 2014)
We study the existence of nonnegative solutions for a system of impulsive differential equations subject to nonlinear, nonlocal boundary conditions. The system presents a coupling in the differential equation and in the boundary conditions. The main tool that we use is the theory of fixed point index for compact maps.